Desempenho em Matemática e as disparidades de gênero no mercado de trabalho: evidências para o Ceará - Silva, Arthur Monteiro da (2022)
This paper seeks to contribute to the literature by investigating the relationship between gender inequalities in mathematics and wage and occupational disparities in the labor market, so far, not addressed in other studies. To this end, a longitudinal follow-up of students graduating from public schools in Ceará in 2012 to 2014 and entering the labor market in 2019 was conducted. This research used the SPAECE database from the Secretary of Basic Education of the State of Cearáá, the School Census, and RAIS data provided by the Ministry of Labor and Employment. To verify the effects of mathematics performance on income differentials, participation in the formal market and in the market in the areas of Science, Technology, Engineering and Mathematics (STEM), the following methods were used: Oaxaca-Blinder Decomposition and Entropy Balancing. From the results, it was observed that the disparities in the math performance of young people are relevant to understanding gender disparities in the labor market for this audience. By equating girls with boys in cognitive skills in mathematics, it was found that wage and occupational inequalities reduced between these groups. Math skills also positively influence the probability of being in the labor market, and reduce the gender gap in young people.